2011
DOI: 10.1210/jc.2011-0272
|View full text |Cite
|
Sign up to set email alerts
|

In SilicoAnalysis Identifies a Novel Role for Androgens in the Regulation of Human Endometrial Apoptosis

Abstract: Context:The endometrium is a multicellular, steroid-responsive tissue that undergoes dynamic remodeling every menstrual cycle in preparation for implantation and, in absence of pregnancy, menstruation. Androgen receptors are present in the endometrium.Objective:The objective of the study was to investigate the impact of androgens on human endometrial stromal cells (hESC).Design:Bioinformatics was used to identify an androgen-regulated gene set and processes associated with their function. Regulation of target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 41 publications
(70 reference statements)
5
63
0
Order By: Relevance
“…Functional studies confirmed that treatment of human primary ESCs in vitro with the potent androgen DHT significantly decreased cell proliferation and migration as well as AR-dependent inhibition of staurosporin-induced apoptosis (Marshall et al 2011). Similar effects on proliferation were observed in vitro with human primary endometrial epithelial cells treated with the weak androgen A4; A4 induced a dosedependent decrease in proliferation evident by decreased uptake of 3 H-thymidine and MKi67 expression, an effect that was reversed after co-incubation with the AR antagonist cyproterone acetate (Tuckerman et al 2000).…”
Section: Proliferationmentioning
confidence: 70%
See 3 more Smart Citations
“…Functional studies confirmed that treatment of human primary ESCs in vitro with the potent androgen DHT significantly decreased cell proliferation and migration as well as AR-dependent inhibition of staurosporin-induced apoptosis (Marshall et al 2011). Similar effects on proliferation were observed in vitro with human primary endometrial epithelial cells treated with the weak androgen A4; A4 induced a dosedependent decrease in proliferation evident by decreased uptake of 3 H-thymidine and MKi67 expression, an effect that was reversed after co-incubation with the AR antagonist cyproterone acetate (Tuckerman et al 2000).…”
Section: Proliferationmentioning
confidence: 70%
“…Although AR is expressed at low levels in endometrial epithelial cells during the secretory phase, the endometrium of women administered with the anti-progestin mifepristone exhibits an elevated expression of AR in epithelial and stromal cells (Slayden et al 2001, Narvekar et al 2004. Notably, analysis of full-thickness uterine biopsies demonstrates that AR immunoexpression in endometrial epithelial cells is increased following progesterone withdrawal at the time of menses, consistent with role for progestins in regulating the expression of AR (Marshall et al 2011). Following the establishment of pregnancy, immunohistochemistry studies have reported that AR is detected in decidual stromal cells and in endothelial cells lining endometrial arteries in first-trimester decidua (Horie et al 1992, Milne et al 2005, Critchley & Saunders 2009).…”
Section: Ar-dependent Signalling and Ar Expression In The Endometriummentioning
confidence: 77%
See 2 more Smart Citations
“…In the nonmalignant endometrium, AR was reported to be expressed in the endometrium throughout the menstrual cycle (Mertens et al 2001, Apparao et al 2002, Ito et al 2002, Marshall et al 2011, Gibson et al 2014. The status of AR immunoreactivity in stromal cells is higher than that of epithelial AR throughout the menstrual cycle (Apparao et al 2002).…”
Section: Androgen Receptor Expressionmentioning
confidence: 99%